Gut content analysis of three cardinalfishes, Cheilodipterus quinquelineautus (Cuvier, 1828), Sphaeramia nematopiera (Bleckjer, 1856) and Fibramia thermalis (Cuvier, 1829) in Palompon, Leyte, Philippines - Sermonia, Jessa Loraine S.
The feeding habits of three cardinalfishes Cheilodipterus quinquelineatus (, Sphaeramia nematoptera, and Fibramia thermalis, have been studied through analysis of gut contents. The gut contents were examined and percentage of chyme and non-chyme were measured wherein non-chyme components were identified and classified into taxonomical groups. Results show that more than 60% of the gut contents for all three species were chime and the remaining percentage were the non-chyme. Fish bones (32%), Fish eggs (22%), Fish (9%), Shrimp (9.06%), and Forams (7.06%) were the most abundant prey items in C. quinquelineatus. For S. nematoptera, Copepodspecies dominated in which Cyclopoid composed 85% of prey item per gut, followed by Harpacticoid (2.93%), Calanoid (2.90%), Gammarid (2.8%), and Polychaete (1.2%). Mysid (53%), Harpacticoid (22%), and Gammarid (6%) were the top three abundant prey items for Fibramia thermalis, followed by Tanaid (4.4%) and Polychaete(2.6%). These show that C. quinquelineatus prey on larger organisms such as fishes, as compared to S. nematoptera and F. thermalis that feeds of smaller organisms such as the copepods. These results implies that there are similarities but at low relative frequency on the type of prey items they feed on, thus indicates the existence of resource partitioning among the species that resorts to difference in abundance of the prey items that signifies less competition in terms of food resource.